PENGARUH RESTRUKTURISASI MELALUI PEMBENTUKAN HOLDING BUMN TERHADAP KINERJA KEUANGAN BUMN - Ryan Ardany Sumarna; Akhmad Solikin (SUBSTANSI, 2018)
State-owned enterprises (SOEs) have additional duties to participate in accelerating development and supporting national economic growth in addition to being profit oriented companies. Various strategies to improve performance of the SOEs can be implemented, including restructuring through the establishment of SOEs holding. Several SOEs active in the same sectors were regrouped to become a holding company so that management is expected to become more optimal. In Indonesia until 2016, four SOEs, i.e. PT Semen Indonesia (Persero) Tbk., PT Pupuk Indonesia (Persero), Perum Perhutani and PT Perkebunan Nusantara III (Persero) have been established as holding companies. It is expected that the holdings will improve their financial performance. This article aims at evaluating whether the financial improvements happened by employing fixed effect panel data model. The results show that holding affect financial performances in terms of profitability, leverage, and liquidity. Profitability deteriorated after holding, while leverage and liquidity showed mixed results.